Why do I have to say what my sexual orientation is if I just want to take a vacation? Experience and expectations of young Italian LGBTQ tourists - Bartoletti, Roberta; Giannini, Lorenzo (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
The traveller’s experience is still somewhat under investigated in research into LGBTQ tourism, and qualitative research on LGBTQ tourists along with disciplinary approaches in the field of the sociology of consumption are rare, also in Italy. We present the results of an exploratory study based on a set of 50 interviews and 2 focus groups with young non heterosexual individuals. A total of 29 gay men and 26 lesbians were interviewed, aged 19-31 years. The interviews were performed by graduate students under the framework of a Sociology of Consumption workshop throughout November and December 2017. The objective of our research is to collect accounts of the holiday experiences of young Italian gay and lesbian tourists and gather information regarding their needs and feelings, focusing on the relationship between sexuality, identity and travel. In particular, our research question is if consumption can really be a vehicle of identification and social inclusion. Moreover, we wonder if, and how, inclusion and identification functions across the “LGBTQ/gay friendly” and “LGBTQl/gay only” offers, that are perceived in an ambivalent way by our interviewees.